THE ANALYSIS OF GRAMMATICAL ERRORS IN SPEAKING BY STUDENTS OF MADRASAH ALIYAH DARUL HIJRAH PUTRA ISLAMIC MODERN BOARDING SCHOOL MARTAPURA - Andrea Chandra; Hidayatullah Hidayatullah (Intensive Journal, 2018)
This study aims to reveal the factors and types of grammatical errors are made by students at The Islamic Boarding School of Darul Hijrah. Throught this research, educators or education practitioners are expected To make the results of this research as a material to identify and solve problems especially grammar and speaking and as a learning model that can be used, especially for boarding school or madrasah that have similar characteristics or the same as  The  Islamic  Boarding School  of Darul  Hijrah.  This  study was  conducted in  a descriptive using qualitative approach at Madrasah Aliyah of Darul Hijrah Putra Islamic Modern Boarding School Martapura where the eleventh grade students of Madrasah Aliyah Islamic Boarding School of Darul Hijrah Putra are sellected as the subject of this research. The data was collected by observation, interview, and documentation. The result of this research are  the students were still confused in making the agreement between subject and verb,  in differentiating whether to use the definite or indefinite articles, in deciding preposition which preposition should be used, whether to use in, on, or at. Confused in deciding which pronoun should be used to substitute nouns, whether it is personal, relative, possessive, or demonstrative pronouns. The students over generalized the pluralizing of nouns. They just added the -s/ -es without considering that there are some irregular forms of nouns pluralization. The students applied rules in forming past time verb to conjunctions. Some  factors  caused are he lack of vocabularies and grammar knowledge.